Predicting sexual intention to engage in premarital sex among late adolescent in Kuantan government secondary schools: an application of the Theory of Planned Behavior - Abdullah, Fa’iza; Draman, Samsul; Zainuddin, Nur Akmanidar; Abd. Aziz, Karimah Hanim; Muhammad, Noor Azimah (2018)
To measure the prevalence of premarital sexual experience among late adolescent in Kuantan To determine the socio cognitive factors to engage in premarital sex behavior amongst late adolescent in Kuantan